Politikwandel und Konvergenz in der Umweltpolitik, 1950-2000 = Policy change and convergence in environmental policy - Busch, P.-O.; Jörgens, H. (Politische Vierteljahresschrift, 2007)
The authors examine the convergence of national environmental policies. They investigate the international spread of 22 environmental policy innovations across 43 countries and of 8 environmental policy innovations worldwide. On this empirical basis, recurring patterns in the global spread of environmental policy innovations are identified and linked to specific causal mechanisms through which this change occurs. In particular, the authors demonstrate how and to what extent diffusion, harmonization and imposition matter as mechanisms of international and global environmental policy convergence.